2013
DOI: 10.1155/2013/381910
|View full text |Cite
|
Sign up to set email alerts
|

Some Pharmacodynamic Aspects of Cefepime

Abstract: Some pharmacodynamic effects of cefepime, a new injectable semisynthetic cephalosporin, were studied in laboratory animals and the following results were obtained. Cefepime maximally stimulated isolated guinea pig's ileum, rat's colon (80 μg/mL bath), and rabbit's duodenum (400 μg/mL bath). Contrarily, complete relaxation of isolated rat's fundic strip was produced by 80 μg/mL bath. Effects of cefepime on isolated rat's uterine muscle were different according to stage of sex cycle. Cefepime did not induce any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…This was evidenced by the decline in rat's feverish BT induced after s.c. administration of Brewer's yeast suspension. This effect seemed to be mediated centrally through an action on the heat-regulating center in such a manner to increase heat loss by peripheral vasodilatation of skin blood vessels, as well as the direct vascular relaxant and negative inotropic effect of cefepime (Elsayed et al, 2013). This finding is consistent with that recorded by Goto et al who recorded cefepime-induced significant hypothermia in mice (Goto et al, 1992).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This was evidenced by the decline in rat's feverish BT induced after s.c. administration of Brewer's yeast suspension. This effect seemed to be mediated centrally through an action on the heat-regulating center in such a manner to increase heat loss by peripheral vasodilatation of skin blood vessels, as well as the direct vascular relaxant and negative inotropic effect of cefepime (Elsayed et al, 2013). This finding is consistent with that recorded by Goto et al who recorded cefepime-induced significant hypothermia in mice (Goto et al, 1992).…”
Section: Discussionsupporting
confidence: 85%
“…Analgesics, antipyretics, and others are generally prescribed along with antibiotics for the remediation of systemic infections with fever and pain. However, many antibiotics including cefepime have other pharmacological actions like reducing spontaneous locomotor activity, relaxing the skeletal muscles, stimulating intestinal movements, potentiating anesthesia in mice, inducing significant hypothermia and analgesia (Elsayed et al, 2013;Goto et al, 1992;Kadota et al, 1992). Hasegawa et al showed that cefadroxil inhibited gastric secretion and raised the biliary secretion in rats (Hasegawa et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The kidney is an important organ that the body needs to perform several important functions including maintaining balance, regulating of the extracellular environment, such as detoxification and excretion of toxic metabolites and drugs (Ferguson et al, 2008). Due to its high vessels and complex metabolic activities, many drugs and environmental antibiotics cause toxicity of the kidney (Elsayed et al, 2014). Diagnose kidney disease with objective measures of kidney damage and function has been recognized as a major burden to public health.…”
Section: Introductionmentioning
confidence: 99%